Historical aspects and current challenges of Physical Education policies: a survey of Brazilian programs and actions (Research, Society and Development, 2020)
The Physical Education (PE) policies in Brazil have been poorly explored and discussed. Health, education, and sports are areas of knowledge sustained by PE. However, it has not been addressed together, as the PE field purpose. The aim was to present an overview of the main historical aspects of PE policies, by systematizing their technical and operational aspects and unveil the challenges in Brazil. The research did a data extraction, which characterized as a policy analysis in the process of organizational and operational information. Additionally, a bibliography review was applied to support the discussion. The actual public programs in Brazil are established since 1995 to 2017, and most of them prioritize a specific stratum of the population to develop actions and usually cover the national territory. Actions linked to moments and not temporal construction. Finally, Brazil has a large in the evaluation and monitoring of policies around PE. For future application an alternative is the unification of political sectors to favor environments and practices to meet the current demands of society, promoting a continuing and multidisciplinary professional training and link actions beyond the public sector.